2006
DOI: 10.1029/2005jc003392
|View full text |Cite
|
Sign up to set email alerts
|

Simulating tropical river plumes, a set of parametrizations based on macroscale data: A test case in the Mekong Delta region

Abstract: [1] A year-long simulation of the Mekong river plume is conducted. The purpose is to identify the main processes impacting the fate of tropical freshwater runoff onto the shelf for later inclusion into a global ocean circulation model. Factors influencing the river plume in a general case are listed and are included in a coastal ocean configuration of the Princeton Ocean Model. This is achieved either explicitly, as for wind forcing, or using parametrizations corresponding to the length and timescales of river… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…However, the plume never extends further than 20 km from the coast, which is the limit of the subaqueous delta. Our results are consistent with those from Hordoir et al [33], who showed that the plume of the Mekong River is dominated by geostrophy from a dynamical perspective, with freshwater advected by a coastally trapped baroclinic current. This behavior was confirmed by a Rossby number less than 1 throughout the year, due to the large freshwater discharge.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, the plume never extends further than 20 km from the coast, which is the limit of the subaqueous delta. Our results are consistent with those from Hordoir et al [33], who showed that the plume of the Mekong River is dominated by geostrophy from a dynamical perspective, with freshwater advected by a coastally trapped baroclinic current. This behavior was confirmed by a Rossby number less than 1 throughout the year, due to the large freshwater discharge.…”
Section: Discussionsupporting
confidence: 83%
“…Southern estuaries in the case of SW waves in the low flow season (Figure 3f) and in the case of Southern waves in the flood season (Figure 4e). Globally, the river plume is very narrow and its extent is reduced throughout the year (as also shown by Loisel et al [25]) for two reasons: (1) most of the particles carried by the river settle in the lower estuary or around the river mouths; (2) the plume is constrained along a baroclinic coastal current as demonstrated by Hordoir et al [33]. Differences between low flow and flood seasons are small because the turbidity patterns are driven by wave action, more than by the river flow.…”
Section: Temporal Variation Of Sscmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, the wind‐driven circulation of freshwater is not affected by any increase of the stratification and extends over the entire mixed layer which explains the low advection velocities. If the release of freshwater occurs in a sea with higher salinity, the current structure will, on shorter time scales, be affected by the presence of juvenile freshwater [ Fong and Geyer , 2001; Hordoir et al , 2006]. During the advection in the Baltic proper, freshwater can be considered as a passive tracer providing information on the variability of the large‐scale circulation.…”
Section: Resultsmentioning
confidence: 99%
“…Zu et al (2014) pointed out that wind determines the horizontal shape and spreading of the plume by wind-driven coastal currents. Winds and ambient wind-driven current play important roles in transporting the freshwater downstream (Dong et al, 2004;Fong & Geyer, 2002;Gan et al, 2009;Hordoir et al, 2006). For instance, a study of Merrimack River plume by Kakoulaki et al (2014) shows that the plumes with scales less than 12 km are sensitive to wind direction when wind speed exceeds 4 m/s.…”
Section: River Plumesmentioning
confidence: 99%